Insight into the origin of lithium/nickel ions exchange in layered Li(NixMnyCoz)O2 cathode materials. (July 2018) - Xiao, Yinguo; Liu, Tongchao; Liu, Jiajie; He, Lunhua; Chen, Jie; Zhang, Junrong; Luo, Ping; Lu, Huaile; Wang, Rui; Zhu, Weiming; Hu, Zongxiang; Teng, Gaofeng; et al.
Abstract: In layered LiNix Mny Coz O2 cathode material for lithium-ion batteries, the spins of transition metal (TM) ions construct a two-dimensional triangular networks, which can be considered as a simple case of geometrical frustration. By performing neutron powder diffraction experiments and magnetization measurements, we find that long-range magnetic order cannot be established in LiNix Mny Coz O2 even at low temperature of 3 K. Remarkably, the frustration parameters of these compounds are estimated to be larger than 30, indicating the existence of strongly frustrated magnetic interactions between spins of TM ions. As frustration will inevitably give rise to lattice instability, the formation of Li/Ni exchange in LiNix Mny Coz O2 will help to partially relieve the degeneracy of the frustrated magnetic lattice by forming a stable antiferromagnetic state in hexagonal sublattice with nonmagnetic ions located in centers of the hexagons. Moreover, Li/Ni exchange will introduce 180° superexchange interaction, which further relieves the magnetic frustration through bringing in new exchange paths. Thus, the variation of Li/Ni exchange ratio vs. TM mole fraction in LiNix Mny Coz O2 with different compositions can be well understood and predicted in terms of magnetic frustration and superexchange interactions. This provides a unique viewpoint to study the Li/Ni ions exchange in layered Li(Nix Mny Coz )O2 cathode materials. Graphical abstract: Li/Ni exchange ratios in series of LiNix Mny Coz O2 materials are precisely determined for the first time through high resolution neutron diffraction experiments. Based on the correlated relation between Li/Ni exchange ratio and strengthen of magnetic frustration, we argue that Li/Ni exchange can act as an effective way to release the frustration in LiNix Mny Coz O2 .fx1 Highlights: Li/Ni exchange ratios in LiNix Mny Coz O2 are precisely determined through high resolution neutron powder diffraction method. Relationships between Li/Ni exchange ratio and compositions of LiNix Mny Coz O2 materials are clarified. The LiNix Mny Coz O2 materials are proved to be strong magnetically frustrated system. Li/Ni exchange can act as an effective way to relieve the frustration in LiNix Mny Coz O2 .